An introduction to teaching in UK higher education : a guide for international and transnational teachers - Byrne, Nuala, 1966-; Butcher, Christopher, 1951- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Covering everything you need to know about teaching within the UK higher education system, this book is the ideal introduction for anyone looking to start their teaching career. A must-read guide for international staff new to teaching in UK higher education, this key text focusses on what is particular and often baffling to those who are new to higher education teaching in the UK. With practical tips and advice rooted in relevant theory, it is an invaluable resource to guide through the initial teaching experience. Breaking down all of the aspects involved in teaching learning and assessing in UK higher education, this book covers: The key features of UK higher education - particularly how it might differ from other systems; How courses and the curriculum are designed; How to support learning within your teaching practice; Advice on marking and giving worthwhile feedback; How to develop your own professional practice; A full glossary of key terms. An Introduction to Teaching in UK Higher Education is a one-stop resource for those looking to begin a career in UK higher education. Particularly useful for new international staff, it will also be of interest to those looking to improve their teaching practice"--
Key features of UK higher education -- Education in the UK -- How students learn and what the implications are for teaching -- Curriculum and course design -- Teaching for supporting learning -- Assessing and giving feedback -- Supporting students -- On-going development of your professional practice -- Key terms, glossaries and abbreviations.
OCLC-licensed vendor bibliographic record.
Keywords: College teachers, Foreign -- Vocational guidance -- Great Britain; College teaching -- Great Britain; Education, Higher -- Great Britain; EDUCATION / General